Endogenous Mesenchymal Stromal Cells in Bone Marrow Are Required to Preserve Muscle Function in mdx Mice. (17th February 2015) - Fujita, Ryo; Tamai, Katsuto; Aikawa, Eriko; Nimura, Keisuke; Ishino, Saki; Kikuchi, Yasushi; Kaneda, Yasufumi
Abstract: The physiological role of "endogenous" bone marrow (BM) mesenchymal stromal cells (MSCs) in tissue regeneration is poorly understood. Here, we show the significant contribution of unique endogenous BM-MSC populations to muscle regeneration in Duchenne muscular dystrophy (DMD) mice (mdx). Transplantation of BM cells (BMCs) from 10-week-old mdx into 3–4-week-old mdx mice increased inflammation and fibrosis and reduced muscle function compared with mdx mice that received BMCs from 10-week-old wild-type mice, suggesting that the alteration of BMC populations in mdx mice affects the progression of muscle pathology. Two distinct MSC populations in BM, that is, hematopoietic lineage (Lin) − /ckit − /CD106 + /CD44 + and Lin − /ckit − /CD106 + /CD44 − cells, were significantly reduced in 10-week-old mdx mice in disease progression. The results of a whole-transcriptome analysis indicated that these two MSC populations have distinct gene expression profiles, indicating that the Lin − /ckit − /CD106 + /CD44 + and Lin − /ckit − /CD106 + /CD44 − MSC populations are proliferative- and dormant-state populations in BM, respectively. BM-derived Lin − /CD106 + /CD44 + MSCs abundantly migrated to damaged muscles and highly expressed tumor necrosis factor-alpha-stimulated gene/protein-6 (TSG-6), an anti-inflammatory protein, in damaged muscles. We also demonstrated that TSG-6 stimulated myoblast proliferation. The injection of Lin − /ckit − /CD106 + /CD44 + MSCs into the muscle of mdx mice successfully ameliorated muscle dysfunction by decreasing inflammation and enhancing muscle regeneration through TSG-6-mediated activities. Thus, we propose a novel function of the unique endogenous BM-MSC population, which countered muscle pathology progression in a DMD model. Stem Cells 2015;33:962–975